PREDICTIVE MARKETING MIX MODELLING IN FMCG PACKAGED FOOD CATEGORY INCLUDING PRICE AND ADVERTISING IMPACT - Kolanowski, Tomasz M. (Metody Ilościowe w Badaniach Ekonomicznych, 2009)
Case study describing estimation of Marketing Mix econometricsales modelling on packaged food fast moving consumer goods product.Model bases on two step modelling approach, using ordinary least squaresmethod. Adstock data transformation has been used to evaluate advertisingimpact with time distributed lag. Paper presents non-linear relations betweenmarket distribution, consumer price levels and advertising as well as 52weeks forward sales forecast accuracy evaluation